Effect of Leg Length Discrepancy on Lateral Center-edge Angle Measurement. Issue 3 (20th March 2022) - Park, Jung-Wee; Shin, Chang Ho; Choi, Byung Sun; Cho, Yoon Joo; Yoo, Won Joon; Choi, In Ho; Cho, Tae-Joon
Abstract : Background: In patients with leg length discrepancy (LLD) and consequent pelvic obliquity, either the longitudinal axis of the pelvis or a line perpendicular to the ground may be used as the longitudinal reference line for measuring the lateral center-edge angle (LCEA). We aimed to (1) systematically inspect which longitudinal reference line has been used for measuring the LCEA in previous studies; (2) evaluate the frequency of change in the radiographical classification of acetabular overcoverage or undercoverage per the longitudinal reference line; and (3) validate the trigonometric method, predicting the change in the LCEA according to the LLD. Methods: Studies investigating the LCEA published between January 1976 and July 2019 in the MEDLINE database were categorized according to the longitudinal reference line used. Further, in a retrospective analysis of 238 patients surgically treated for LLD, the LCEA was first measured on standing pelvic radiographs using the longitudinal axis of the pelvis (pLCEA) and measured again using a line perpendicular to the ground (gLCEA). Femoral head coverage was categorized as undercoverage, normal, or overcoverage based on the pLCEA and gLCEA. The theoretically calculated difference between the pLCEA and gLCEA (dLCEA) as determined using a trigonometric method was compared with the dLCEA measured on radiographs. Results: Of 229 previous studies, 188 did not specify the longitudinal reference line. The number of patients who were diagnosed with acetabular overcoverage using the pLCEA and gLCEA was one and fourteen, respectively ( P <0.001). The number of patients who were diagnosed with acetabular undercoverage using the pLCEA and gLCEA was one and zero, respectively ( P =1.000). There was no difference ( P =0.433) between the theoretically calculated (9±5 degrees) and measured (9±5 degrees) dLCEAs. Conclusions: The definition of the longitudinal reference line should be clarified when measuring the LCEA. The trigonometric method can accurately predict the change in the LCEA according to LLD in concentric hips without proximal femoral and pelvic deformities. Level of Evidence: Level IV—diagnostic study.